Phenomenological Interpretation of Social Verses: Revealing the Value of Humanism in Surah Al-Hujurat - Abdul Jabar; Nur Arfiyah Febriani; Mohammad A’mmar Bin Mohd Naim; Saepul Saepul; M. Zulfani Hidayat (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study explores the humanistic and social values of Surah al-Hujurat through a phenomenological interpretation of the Qur’an. The phenomenological approach aims to understand the Qur’an not merely as a normative text, but as a lived reality that reveals human consciousness within social life. Surah al-Hujurat contains essential ethical principles of Islamic society such as tabayyun (verification of information), ukhuwah (brotherhood), the prohibition of mockery and backbiting, and human equality based on taqwa (piety). Through phenomenological analysis, these values are shown to represent existential awareness that connects human beings with divine and social realities. They constitute what is known as Qur’anic humanism a form of humanity rooted in monotheism (tawhid) and manifested in social ethics. The study concludes that a phenomenological reading of Surah al-Hujurat is relevant for fostering moral and social consciousness amid disinformation and ethical crises in the modern digital era. The main contribution of this study lies in offering a phenomenological reading model of Surah al-Hujurat that remains underexplored in prior tafsir scholarship, while proposing the conceptual framework of Qur’anic humanism as an alternative to the predominantly normative approaches that have characterized studies of its social verses.